Amorphous complexions enable a new region of high temperature stability in nanocrystalline Ni-W. (September 2018) - Schuler, Jennifer D.; Donaldson, Olivia K.; Rupert, Timothy J.
Abstract: Solute segregation is used to limit grain growth in nanocrystalline metals, but this stabilization often breaks down at high temperatures. Amorphous intergranular films can form in certain alloys at sufficiently high temperatures, providing a possible alternative route to lower grain boundary energy and therefore limit grain growth. In this study, nanocrystalline NiW that is annealed at temperatures of 1000 °C and above, then rapidly quenched, is found to contain amorphous intergranular films. These complexions lead to a new, unexpected region of nanocrystalline stability at elevated temperatures. Graphical abstract: Unlabelled Image